A Feasibility Study on the Transmutation of 100Mo to 99mTc with Laser-Compton Scattering Photons. (2nd January 2018) - Lee, Jiyoung; Rehman, Haseeb ur; Kim, Yonghee
Abstract: This paper evaluates the effectiveness of producing 99 Mo using the photonuclear giant dipole resonance (GDR) (γ, n) reaction. The focus of the study is a novel implementation of the photonuclear transmutation method by the use of laser-Compton scattering (LCS) gamma-ray beams to produce 99 Mo. The use of LCS enables the production of energetic and high-intensity gamma rays with a tunable energy spectrum based on various facility parameters (i.e., electron energy, laser energy, and collimation angle). The combination of these three features have made the use of the LCS process for the production of 99 Mo using the photonuclear (γ,  n) reaction a concept deserving further investigation. In this study, rigorous optimization of the LCS spectrum is performed to maximize the overlapping of the GDR cross section and the LCS spectrum to optimize the production rate and activity of the 99 Mo product. Furthermore, the unique innovation of the multiple laser extraction concept is also included in this paper in order to increase the gamma-ray intensity by a factor of 10 to 20.